Formulation And In-Vitro Evaluation Of Gliclazide Oro-Dispersible Tablets - Thabassum, Farheen; Chinthala , Praveena (Journal of Neonatal Surgery, 2025)
Introduction: Gliclazide is a second-generation sulfonylurea used for the management of type II diabetes mellitus. Due to its poor water solubility, the onset of action may be delayed. The primary objective of the present study was to formulate Gliclazide oro-dispersible tablets (ODTs) to enhance solubility and dissolution rate, thereby promoting a faster onset of therapeutic action. Methods: Gliclazide ODTs were formulated using the direct compression method with three different superdisintegrants: Crospovidone, Sodium Starch Glycolate (SSG), and Croscarmellose sodium. A total of nine formulations were developed. Differential Scanning Calorimetry (DSC) was performed to evaluate potential drug–excipient interactions. All formulations were assessed for physicochemical properties, in vitro drug release, and release kinetics. The optimized formulation was further subjected to a 6-month stability study under ICH-recommended conditions. Results: All formulations complied with pharmacopeia specifications. Among them, formulation F3 exhibited the fastest disintegration time (19.1 seconds) and achieved 99.31% drug release within 15 minutes, attributed to the efficient wicking and swelling properties of crospovidone. Based on disintegration time and drug release performance, F3 was identified as the optimized formulation. It remained physically and chemically stable over a 6-month period. Conclusion: Gliclazide ODTs were successfully developed using direct compression and superdisintegrants such as Crospovidone, SSG, and Croscarmellose Sodium. The optimized formulation (F3) demonstrated rapid disintegration, enhanced drug release, and stability over 6 months, indicating its potential for improved patient compliance and faster therapeutic onset in the treatment of type II diabetes